Influence of Culture Environment and Mollicutes Contaminations on CD133 Modulation in Cancer Stem Cells - Mariotti, Elisabetta; Mirabelli, Peppino; D’Alessio, Francesca; Gemei, Marica; Noto, Rosa Di; Fortunato, Giuliana; Vecchio, Luigi Del (IntechOpen, 2011)
None